Unilateral thalamic glioma disrupts large-scale functional architecture of human brain during resting state - Li S (Dove Medical Press, 2019)
Sirui Li, Lei Gao, Ying Liu, Yawen Ao, Haibo Xu Department of Radiology, Zhongnan Hospital of Wuhan University, Wuhan University, Wuhan 430071, People’s Republic of China Background: The thalamus is an important deep brain structure for the synchronization of brain rhythm and the integration of cortical activity. Human brain imaging and computational modeling have non-invasively revealed its role in maintaining the cortical network architecture and functional hierarchy. Purpose: The objective of this study was to identify the effect of unilateral thalamic damage on the human brain intrinsic functional architecture. Patients and methods: We collected an 8-minute resting-state functional magnetic resonance imaging (R-fMRI) data on a 3.0 T magnetic resonance scanner for all the participants: a preoperative patient with left thalamus destroyed by anaplastic astrocytoma (WHO grade III type of astrocytoma) and 20 matched healthy controls. The R-fMRI data was analyzed for functional connectivity and amplitude of spontaneous fluctuations. Results: The patient showed prominent decrease in functional connectivity within primary sensory networks and advanced cognitive networks, and extensive alterations in between-network coupling. Further analysis of the amplitude of spontaneous activity suggested significant decrease especially in the topographies of default mode network and the Papez circuit. Conclusion: This result provided evidence about the consequences of thalamic destruction on the correlation and landscape of spontaneous brain activity, promoting our understanding of the effects of thalamic damage on large-scale brain networks. Keywords: brain networks, functional connectivity, default mode network, Papez circuit